Gut microbiota contribute to high-altitude adaptation in tree sparrows - Tingbei Bo; Gang Song; Mengru Zhang; Xiaoming Xu; Jundong Duan; Huishang She; Yun Fang; Wenting Li; Jing Wen; Jingsong Liu; Dehua Wang; Fumin Lei (mSystems)
ABSTRACT The intricate relationship between gut microbiota and various physiological functions in animals has emerged as a focal point in understanding host adaptability. Unlike the native birds of the Qinghai-Tibet Plateau (QTP), the tree sparrow (Passer montanus) is believed to have colonized the plateau within the last few thousand years. Given the vast expanse and harsh conditions of the plateau, the role of gut microbiota in facilitating the tree sparrow’s adaptation to this high-altitude habitat remains largely unexplored and holds significant scientific interest. Therefore, we employed a multidisciplinary approach combining amplicon sequencing, transcriptome analysis, and fecal microbiota transplantation (FMT) to investigate the functional role of gut microbiota in high-altitude tree sparrows across different seasons. Results indicate that the gut microbiota of tree sparrows exhibits seasonal and altitude-dependent changes, with an increase in Lactobacillus in winter, which may promote heat production to cope with the cold. FMT experiments confirmed that "high-altitude gut microbiota" enhances the expression of heat-related proteins (avUCP) and upregulates heat-related genes syt1 and chodl. These findings suggest an adaptive strategy whereby tree sparrows utilize their gut microbiota to modulate energy metabolism, ultimately conserving energy in the resource-limited high-altitude environment.IMPORTANCEThis study provides one evidence that gut microbiota mediates high-altitude adaptation in tree sparrow. By integrating multi-omics and fecal transplantation in tree sparrows (Passer montanus)—a species invading the Qinghai-Tibet Plateau within millennia—we reveal seasonally dynamic microbial strategies critical for survival in extreme environments. These findings establish gut microbiota as a key driver of rapid altitudinal adaptation, offering new insights into how microbial functions enable vertebrate range expansion into challenging ecosystems. The mechanistic framework also informs conservation strategies for wildlife facing climate-driven habitat shifts.